Promoting Clinical Breast Examination as A screening Tool for Breast Cancer in Iraq - Al-Alwan, nada; mualla, Faisal (Iraqi National Journal of Nursing Specialties, 2014)
Breast cancer constitutes about one fourth of the registered cancer cases among the Iraqi population (1) and it is the leading cause of death among Iraqi women (2) . Each year more women are exposed to the vicious ramifications of this disease which include death if left unmanaged or the negative sequels that they would experience, cosmetically and psychologically, after exposure to radical mastectomy. The World Health Organization (WHO) documented that early detection and screening, when coped with adequate therapy, could offer a reduction in breast cancer mortality; displaying that the low survival rates in less developed countries, including Iraq, is mainly attributed to the lack of early detection programs coupled with inadequate diagnostic and treatment facilities (3) . Although mammography machines, as main screening tools for breast cancer, are available in the major hospitals in each province in Iraq, yet those are mainly used for diagnostic purposes in patients who present with palpable breast lumps. Obviously, due to cost effective measures, lack of resources and the economical challenges that Iraq is facing, it is not expected that the authorities could provide mammography devices across every health care centre in the country to be used for screening of all Iraqi women. Accordingly, promoting other feasible tools could support in solving that dilemma. Clinical Breast Examination (CBE) for women, by highly trained health care providers in Primary Health Care Centers, along with diagnostic mammography in the major hospitals for referred cases, could offer cost effective approaches for early detection of breast cancer in Iraq. The resources required to provide these services are within the reach of all countries with limited resources (4) . The issue of raising awareness on breast cancer and its early detection measures needs to be addressed. Observations reported in Iraqi studies obviously reflect the the limited knowledge of the general population about the disease, its preventive measures and their ignorance regarding the significance of CBE and early medical consultation (5, 6) . Public health awareness campaigns should be endorsed by policy makers to encourage every Iraqi women to look for abnormal signs and symptoms in their breasts and to seek medical advice promptly.